A water-soluble BODIPY based 'OFF/ON' fluorescent probe for the detection of Cd2+ ions with high selectivity and sensitivity. Issue 6 (22nd January 2019) - Maity, Apurba; Ghosh, Utsav; Giri, Dipanjan; Mukherjee, Devdeep; Maiti, Tapas Kumar; Patra, Sanjib K.
Abstract : A simple and readily synthesized BODIPY based fluorescent chemosensor has been developed for the selective and sensitive detection of Cd 2+ ions up to a submicromolar level in aqueous media. Abstract : A water-soluble dilithium salt BODIPY derivative (LiBDP ) with appended dicarboxylate pseudo-crown ether [NO4 ] coordinating sites has been designed, synthesized and characterized successfully for the selective and sensitive recognition of Cd 2+ in aqueous media. The chemosensor exhibits a remarkable increase in fluorescence intensity as well as a distinct color change upon the addition of Cd 2+ over other environmentally and biologically relevant metal ions in H2 O. The fluorometric response ofLiBDP is attributed to the metal chelation-enhanced fluorescence (MCHEF) effect which has been confirmed by a strong association constant of 2.57 ± 1.06 × 10 5 M −1 and Job's plot, indicating 1 : 1 binding stoichiometry betweenLiBDP and Cd 2+ . Frontier molecular orbital analysis (obtained from DFT studies) also illustrates the turn-on fluorescence of the probe by blocking photoinduced electron transfer (PET) after coordination to Cd 2+ . The probe can detect Cd 2+ in a competitive environment up to a submicromolar level in a biologically significant pH range. The sensor is proved to be reversible and reusable by the alternative addition of Cd 2+ followed by S 2− . The OFF / ON / OFF sensing behavior is utilized to construct an INHIBIT molecular logic gate based on the two inputs of Cd 2+ and S 2− and a fluorescence intensity at 512 nm as an output. The test paper experiment demonstrates the practical utility ofLiBDP to monitor Cd 2+ in an aqueous sample. Finally, the sensing probe was utilized to monitor Cd 2+ in living cells.